Phononic Crystal with Adaptive Connectivity. (19th December 2013) - Bergamini, Andrea; Delpero, Tommaso; Simoni, Luca De; Lillo, Luigi Di; Ruzzene, Massimo; Ermanni, Paolo
<x xml:space="preserve">Abstract</x> The band structure of a phononic crystal can be controlled by tuning the mechanical stiffness of the links connecting its constituting elements. The first implementation of a phononic crystal with adaptive connectivity is obtained by using piezoelectric resonators as variable stiffness elements, and its wave‐propagation properties are experimentally characterized. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>